A PHENOMENOLOGICAL STUDY OF ORGANIZATIONAL CULTURE AND EMPLOYEE LOYALTY IN THE CREATIVE INDUSTRY - Maghfiroh, Diana (Journal of Economic Development and Village Building, 2025)
This research aims to explore the meaning of employees' experiences of organizational culture and how it affects job loyalty in the creative industry. Using a qualitative approach with phenomenological methods, this study delves into the perceptions and subjective experiences of employees from three creative companies in Jakarta and Bandung. The results show that an organizational culture that is inclusive, open to innovation, and appreciates individual contributions significantly increases employee loyalty. Values such as freedom of expression, team collaboration, and recognition of work become the foundation of a strong organizational culture in the context of the creative industry. The findings enrich the theoretical understanding of the dynamics of the relationship between organizational culture and employee loyalty, and provide practical recommendations for managers in the creative industry sector in building a sustainable work environment.